2017
DOI: 10.1016/j.aquabot.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Wetland invasion by Typha×glauca increases soil methane emissions

Abstract: 34Wetland invasion by monotypic dominant plants can alter the physicochemical and biological 35 properties of soils that affect methane emissions, a potent greenhouse gas. We examined the 36 effects of Typha × glauca invasion on soil methane using laboratory incubation and controlled 37 mesocosm experiments. Typha-invaded soils collected from three Midwestern (USA) wetlands 38 had greater methane production potential during laboratory incubation than soils dominated by 39 native wet meadow vegetation. Ten y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 48 publications
0
18
1
Order By: Relevance
“…We hypothesized that Typha removal would affect these parameters because previous studies demonstrated that these parameters can be altered by Typha invasion. Specifically, Typha invasion has been linked to higher soil carbon and inorganic nutrients (Angeloni et al ; Jankowski ; Lishawa et al ; Mitchell et al ), increased denitrification rates (Jankowski ; Lishawa et al ), and methane production (Lawrence et al ), and shifts in taxonomic composition of bacterial communities (Angeloni et al ). Therefore, we hypothesized that Typha removal might reverse some of these trends.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We hypothesized that Typha removal would affect these parameters because previous studies demonstrated that these parameters can be altered by Typha invasion. Specifically, Typha invasion has been linked to higher soil carbon and inorganic nutrients (Angeloni et al ; Jankowski ; Lishawa et al ; Mitchell et al ), increased denitrification rates (Jankowski ; Lishawa et al ), and methane production (Lawrence et al ), and shifts in taxonomic composition of bacterial communities (Angeloni et al ). Therefore, we hypothesized that Typha removal might reverse some of these trends.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Typha ‐dominated wetland sites have altered rates of both denitrification (Lishawa et al ) and nitrification (Vale ), as well as shifts in taxonomic composition of bacterial communities (Angeloni et al ) relative to more diverse wetland sites. An increase in methane production has also been documented in sediments from Typha invaded portions of wetlands (Lawrence et al ). Methane is a potent greenhouse gas, so increases in methane production have significant environmental implications.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Further, Carexstricta and Spartinapectinata are fresh-water grown plants; Typhalatifolia and Phragmitesaustralis are species commonly found in fresh to brackish wetlands Clump-forming species; Carexstricta, has higher levels of CH 4 emissions than other growth forms such as clonal dominant grasses [5]. Invasive species like Typhalatifolia produce large amounts of aboveground biomass; Typhalatifolia is associated with increased CH 4 production relative to less productive native communities [6]. Invasive strains of Phragmitesaustralis are a problematic and productive invader of coastal wetlands throughout eastern North America; Phragmitesaustralis is characterized by a high rate of biomass production as well as higher CH 4 emissions as compared to native Phragmites strains and native wetland species [7].…”
Section: Introductionmentioning
confidence: 99%